Understanding the active site in chameleon-like bifunctional catalyst for practical rechargeable zinc-air batteries - Xiongwei Zhong; Xiao Xiao; Qizhen Li; Mengtian Zhang; Zhitong Li; Leyi Gao; Biao Chen; Zhiyang Zheng; Qingjin Fu; Xingzhu Wang; Guangmin Zhou; Baomin Xu (Nature Communications)
Abstract The practical application of rechargeable zinc-air batteries faces challenges stemming from inadequate bifunctional catalysts, contradictory gas-liquid-solid three-phase interfaces, and an ambiguous fundamental understanding. Herein, we propose a chameleon-like bifunctional catalyst comprising ruthenium single-atoms grafted onto nickel-iron layer double hydroxide (RuSA-NiFe LDH). The adaptive oxidation of RuSA-NiFe LDH to oxyhydroxide species (RuSA-NiFeOOH) during charging exposes active sites for the oxygen evolution reaction, while reversible reduction to NiFe LDH during discharge exposes active sites for the oxygen reduction reaction. Additionally, a hierarchical air cathode featuring hydrophilic and hydrophobic layers facilitates the reversible conversion between RuSA-NiFe LDH and RuSA-NiFeOOH, expedites oxygen bubble desorption, and suppresses carbon corrosion. Consequently, our zinc-air batteries demonstrate a high charge/discharge capacity of 100 mAh cm−2 per cycle, a voltage gap of 0.67 V, and an extended cycle life of 2400 h at 10 mA cm−2. We comprehensively elucidate the catalytic reaction thermodynamics and kinetics for the air cathode through electrode potential decoupling monitoring, oxygen bubble desorption tracking, and carbon content quantification.